The Virtual World and Psychological Reality: Examining the Impact of Social Media on Gender and Psychological Well-being - Kinanti, Tira (Psikostudia : Jurnal Psikologi, 2026)
Social media has become an important part of daily life, especially for adolescents and young adults, encompassing communication, self-expression, and identity formation. Studies in Indonesia show that social media affects psychological well-being, particularly among women. This study aims to review the literature regarding the impact of social media on psychological well-being based on gender differences. This research uses a literature study method by searching for publications between 2020 and 2025. The results show that social media affects psychological well-being. Negative impacts are related to excessive use, social comparison, and the internalization of ideal standards, while factors such as self-compassion, emotion regulation, and social support act as protective factors. The findings also show gender-based differences, indicating that women are more often associated with body dissatisfaction and men with masculinity pressure. As an intervention, this study recommends a gender-sensitive multidisciplinary approach, including digital literacy and the practice of mindfulness and self-compassion to improve psychological resilience by promoting better self-awareness and self-acceptance. This approach is expected to serve as a preventive strategy in addressing gender-based social media challenges.